DIRECTIONAL PROTEOLYSIS OF SECONDARY RAW MATERIALS - Zolotarev Nikita A.; Fedotova Olga B.; Agarkova Evgeniya Yu.; Akhremko Anastasya G.; Sokolova Olga V. (Academic Scientific Journal of Chemistry, 2020)
For the food industry, technologies for processing secondary raw materials are of interest. Curd whey is a typical complex secondary bioproduct. It has a high acidity, so it is difficult to recycle. The scope of use of curd whey is limited. There are technologies for processing whey from cheese. In the manufacture of rennet cheese, whey is formed, which is successfully processed. The technology for processing whey from cheese can only partially be applied for processing whey from cottage cheese. In particular, the use of ultrafiltration can be used for the concentration of curd whey protein. The whey protein concentrate from cottage cheese can be hydrolyzed. Curd whey after proteolytic biocatalysis has a higher potential for use in the food industry The use of hydrolyzed whey rather than native is promising. According to studies of domestic and foreign scientists, peptides of medium length (3-10 kDa) have the highest biological value. However, during hydrolysis, a proteolytic process occurs, the consequence of which is the appearance of a bitter taste due to the formation of bitter amino acids. The aim of the study was to obtain a whey protein hydrolyzate with minimally altered sensory characteristics. The problem with whey protein hydrolysis is that a bitter taste appears during hydrolysis. The aim of the study was to obtain a whey protein hydrolyzate of curd whey. The resulting hydrolyzis should not have a bitter taste, and the length of its peptides should be medium. To obtain curd whey hydrolysates with harmonized sensory characteristics, an enzyme preparation from the group of fungal proteases produced by Aspergillus oryzae was selected. The experimental data made it possible to optimize the parameters of the hydrolysis process. The results of the study and analysis confirm that the whey protein hydrolyzate has minimal changes in organoleptic characteristics compared to native serum. In the hydrolyzate there is no bitterness in the taste and aftertaste. It has been proven that the resulting peptides are of medium size.